Função muscular em indivíduos com deficiência isolada do GH devido à mutação no gene do receptor do GHRH - Guimarães, Alana Lalucha de Andrade (2018)
Growth hormone (GH) and insulin-like growth factor type I (IGF-I) show synergistic actions on muscle anabolism. We describe a large cohort of subjects with isolated GH deficiency (IGHD), caused by a mutation in the GH-releasing hormone receptor gene, with low serum levels of GH and IGF-I, and marked reduction of stature and lean mass, despite performing high level of physical activities in the daily life, suggesting satisfactory muscle function. The aim of this study was to assess muscular function in these IGHD subjects. For this purpose, 31 IGHD (16 males) and 40 control (20 males) subjects, matched by age and physical activity, were enrolled. It was assessed lean mass by bioelectrical impedance; muscle strength by dynamometry of handgrip, trunk extension and knee extension; myoelectrical activity and muscle fatigue by fractal dimension, and conduction velocity in vastus medialis, rectus femoris, and vastus lateralis muscles, by surface electromyography. IGHD group showed higher knee extension strength corrected for weight (p<0.001) and conduction velocity of the muscles vastus medialis (p=0.002), rectus femoris (p=0.002) and vastus lateralis (p= 0.05), lower lean mass (p<0.001) and myoelectrical activity of the vastus medialis (p<0.002), rectus femoris (p<0.001) and vastus lateralis (p<0.001). There were no difference between the groups in handgrip and trunk extension corrected for weight in all studied muscles. IGHD group showed moderate significant correlation (p=0.021) between lean mass and knee extensor strength, without significant correlations in the other function parameters. In conclusion, IGHD subjects show greater strength of knee extensors, similar handgrip and trunk extension strength and higher resistance to fatigue, suggesting better muscular function than controls.